2020
DOI: 10.3389/fcell.2020.561703
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of N6-Methyladenosine in the Differentiation of Cancer Stem Cells and Their Fate

Abstract: N6-methyladenosine (m6A) is one of the most common internal RNA modifications in eukaryotes. It is a dynamic and reversible process that requires an orchestrated participation of methyltransferase, demethylase, and methylated binding protein. m6A modification can affect RNA degradation, translation, and microRNA processing. m6A plays an important role in the regulation of various processes in living organisms. In addition to being involved in normal physiological processes such as sperm development, immunity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…(A) Spearman correlation analysis and (B) co-expression network of m6A RNA methylation regulators, methyltransferases (METTL3, METTL14, METTL16, and WTAP), demethylases (FTO and ALKBH5) and 10 m6A-regulated mRNAs in the prognostic signature in TCGA LUAD patient cohorts. Xu et al, 2020). Notably, we observed that most genes with m6A methylation level changes were not accompanied by significant gene expression level changes.…”
Section: Discussionmentioning
confidence: 69%
“…(A) Spearman correlation analysis and (B) co-expression network of m6A RNA methylation regulators, methyltransferases (METTL3, METTL14, METTL16, and WTAP), demethylases (FTO and ALKBH5) and 10 m6A-regulated mRNAs in the prognostic signature in TCGA LUAD patient cohorts. Xu et al, 2020). Notably, we observed that most genes with m6A methylation level changes were not accompanied by significant gene expression level changes.…”
Section: Discussionmentioning
confidence: 69%
“…The sequence near the m6A modification site on the mRNA is highly conservative, mainly occurring on the adenine of the RRACH (R: purine; A: m 6 A; H: non-guanine) sequence, and its function is determined by the methyltransferase (writers: methyltransferase like 3 (METTL3), methyltransferase like 14 (METTL14) and WT1 associated protein (WTAP), et al), demethylase (erasers: fat mass and obesity associated protein (FTO) and alkB homologue 5 (ALKBH5), et al) and binding protein (readers: YTH domain containing family, the insulin like growth factor 2 mRNA binding protein (IGF2BP) family and heterogeneous nuclear ribonucleoproteins A2/B1 (HNRNPA2B1), et al) are jointly regulated ( Yang et al, 2018 ; Li M. et al, 2021 ). M 6 A modification is involved in a variety of biological processes, such as stem cell differentiation, cell division, gametogenesis and biological rhythms, et al, as well as the occurrence of a variety of diseases, including tumors, obesity and infertility ( Xu Y. et al, 2020 ; Zhang M. et al, 2020 ; Song et al, 2020 ). M 5 C modification is another prevalent RNA modification in multiple RNA species, including mRNAs, tRNAs, rRNAs, and ncRNAs ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, inhibitors of FTO and ALKBH5 are being used as candidates for anticancer drug development, especially to inhibit the growth of CSCs by manipulating their m 6 A modification levels. Although these inhibitors have not been tested in clinical trials, they will provide more possibilities for the treatment of cancer (Xu et al, 2020).…”
Section: Prospect Of Clinical Application and Future Researchmentioning
confidence: 99%